Autofluorescence Images with Carl Zeiss versus Topcon Eye Fundus Camera: A Comparative Study - Juan M. Muñoz; Rosa M. Coco; M. Rosa Sanabria; Ruben Cuadrado; Eduardo Blanco (Journal of Ophthalmology)
Purpose. To compare the autofluorescence images of the Zeiss versus Topcon eye fundus cameras and design an objective way to quantify it. Procedures. The IMAGEJ software was used to determine the gray level corresponding to the darkest veins and the peripapillary ring (thresholds), the level of white of the brightest perifoveal area, their difference (contrast level), and the suprathreshold area for each photograph. Results. Carl Zeiss has higher contrast values than Topcon. The Topcon contrast presented a crest with further decline as the suprathreshold area continued to increase. On the contrary, the Zeiss profile did not decline in contrast. Conclusions and Message. The Carl Zeiss camera showed superior contrast ability over the Topcon when performing autofluorescence imaging. We set objective parameters to compare fundus cameras FAF images. These parameters could be the base to objectively measure and determine changes and realize followup to areas of hyper- or hypofluorescence.